Investigating AI-Ethics through Necromancy - An Interdisciplinary Exploration of Uncertainties in Performative Technologies as Curated AI Personas - Hagman, Max; Kalm, Sally (My University, 2026)
This thesis was driven by its uncertain nature, where emerging AI technologies was investigated through Research through Design, Speculative Design and an artistic process. This perspective gave way to exploring solutions that would otherwise have been overlooked as unconventional. The project resulted in an interactive and performative art show, where a debate between four deceased media-philosophers was simulated through the use of Large Language Models. The show’s aesthetics, atmosphere and content all contributed to the User Experience. It was developed iteratively with formative and summative evaluations in form of interviews and surveys, with continuous on-site testing. The critical reflections on AI use-cases resulted in several ethical insights: there is a need to design for responsibility and accountability of generated outcome; there is power in orchestration, as the persons imitated with AI gain importance; there is a need for transparency in training data and agenda; and finally, anthropomorphism contributes to building relationships between humans and machines. Moreover, this thesis also reflects on the possibility of generating new knowledge, and concludes that personified AIs might be a tool to gain lost perspectives on current world states, but will not necessarily generate new knowledge with the current technological limitation. Lastly, This project calls for further research into charismatic AIs and guidelines for social chat-bots, as well as further research into integrity and consent when it comes to simulating people through AI technology.
Keywords: AI, ethics, interaction design, computer science, engineering, art